The rare Axenfeld–Rieger syndrome with systemic anomalies: A case report and brief review of literature. Issue 33 (August 2017) - Song, Wei; Hu, Xiaodan
Abstract: Rationale: Axenfeld–Rieger syndrome (ARS) is a rare autosomal dominant disorder with ocular anterior segment dysgenesis and systemic anomalies. Patient concerns: A 28-year-old Chinese Han female was referred to Beijing Tongren Eye Center for progressive decrease of the visual acuity on her right eye in the past month. Diagnoses: The patient was diagnosed as ARS with retinal detachment based on series of ophthalmic examinations performed. Interventions: A pars plana vitrectomy was performed to manage the retinal detachment. Outcomes: Her best-corrected visual acuity was slightly improved after surgery. Lessons: ARS is a developmental defect of ocular anterior segment with various clinical manifestations which might cause misdiagnosis.